Global Adversities, the Media, and Mental Health - Kesner, Ladislav; Horáček, Jiří (Frontiers in Psychiatry, 2022)
Global communities are currently confronted with a number of complex problems and threats, the reality of which is amplified by the media. These environmental and socio-political stressors have been accompanied by the spread of problematic psychological and behavioural tendencies, such as the growing polarisation of opinions and values, online radicalisation and extremism, deepening xenophobia and nationalism, the proliferation of irrational beliefs and conspiracy theories, and resistance to rational public policy measures. Here we argue that although they fall outside the scope of psychopathology, they nevertheless currently constitute a major challenge for psychiatry as a research domain and a clinical practice. To substantiate this claim, we outline the mechanisms by which media-transmitted stressors impact mental well-being and possibly psychopathology. The common denominator of these global problems and the media’s construction of reality is the increase in uncertainty, unpredictability, and uncontrollability, which prompts defensive responding and, in predisposed individuals, functions as a potent source of chronic stress. These contribute to cognitive inflexibility, a strong predisposing factor for the development of rigid beliefs and attitudes, which to varying degrees underlie the adverse psychological and behavioural tendencies mentioned above. We suggest that the tightening of beliefs and ideas that is the result of cognitive rigidity may correspond to the clinical characteristics of induced delusional disorder. This can be seen as a (ultimately maladaptive) defensive strategy for coping with a high degree of uncertainty and unpredictability. We conclude by briefly outlining the possible ways in which psychiatry can face this challenge.